Effect Of Leguminous Winter Cover Crops On Soil Fertility And Yield Of Summer Maize - Rijal, B; Pandey, KR; Shah, SC; Chaudhary, NK (Agronomy Journal of Nepal, 2021)
A field experiment was conducted at IAAS agronomy farm, Rampur, Chitwan, Nepal from Nov. 2012 to Aug. 2013 to improve soil fertility and production of maize through the inclusion of leguminous winter cover crops in the cropping system. The experiment was conducted for two seasons in single factor randomized complete block design (RCBD) with eight treatments and three replications. Five N fixing legume crops: chickpea (Cicer arietinum), garden pea (Pisum sativum var. sativum), field pea (Pisum sativum var. arvense), lentil (Lens culinaris) and grass pea (Lathyrus sativus); one N fixing legume fodder: Berseem (Trifolium alexandrinum); one non-fixing legume: rajma bean (Phaseolus vulgaris); and maize (as a control) were cultivated in the first season and on the following season maize was cultivated in all plots after incorporating former crop residues. Rajma bean covered the highest area at an early stage but field pea and grass pea covered the maximum land area at a later stage. The highest dry matter production (2.32 t/ha) and nitrogen content in residues (2.57%) were obtained from lentil. Cultivation of leguminous winter cover crops had no significant effect on soil parameters. However, the incorporation of legume residues had significant effects on organic matter content, total nitrogen and available phosphorus in soils. The highest soil organic matter (3.03%) and total nitrogen (0.15%) was observed from field pea plots while the highest available phosphorus (36.00 kg/ha) was from berseem plots. Legumes cultivation and their residues incorporation into the soil had significant effects on grain, straw and dry matter yields of succeeding maize crop. Grain (3.92 t/ha), straw (5.39 t/ha) and dry matter (9.31 t/ha) yields were the highest from lentil plots while the lowest grain (2.51 t/ha), straw (3.96 t/ha) and dry matter (6.48 t/ha) from control plots. Total nitrogen uptake by maize was significant and it was the highest (141.90 kg/ha) from lentil plots and the lowest (109.80 kg/ha) from control plots. Cultivation of lentil in the winter produced satisfactory land coverage and incorporation of its residues into the soil was the best for improving soil fertility and succeeding maize yield under the Chitwan condition of Nepal.